2018
DOI: 10.1371/journal.pone.0204491
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with whole-cell killed or recombinant leishmanial protein and toll-like receptor agonists against Leishmania tropica in BALB/c mice

Abstract: One strategy to control leishmaniasis is vaccination with potent antigens alongside suitable adjuvants. The use of toll-like receptor (TLR) agonists as adjuvants is a promising approach in Leishmania vaccine research. Leishmania (L.) tropica is among the less-investigated Leishmania species and a causative agent of cutaneous and sometimes visceral leishmaniasis with no approved vaccine against it. In the present study, we assessed the adjuvant effects of a TLR4 agonist, monophosphoryl lipid A (MPL) and a TLR7/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…hepatica ES antigens [ 80 ]. Finally, in human vaccine development a new generation of TLR-based adjuvants licensed for use such as MPL (3-O-desacyl-4-monophosohryl lipid A), a detoxified bacterial lipopolysaccharide in aluminium salts, could be a promising source of novel adjuvants in veterinary vaccines [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…hepatica ES antigens [ 80 ]. Finally, in human vaccine development a new generation of TLR-based adjuvants licensed for use such as MPL (3-O-desacyl-4-monophosohryl lipid A), a detoxified bacterial lipopolysaccharide in aluminium salts, could be a promising source of novel adjuvants in veterinary vaccines [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, naltrexone, an opioid receptor antagonist that can shift the immune response toward a Th1 profile induced strong protective Th1 immune responses in mice when administered with alum and F. hepatica ES antigens [80]. Finally, in human vaccine development a new generation of TLR-based adjuvants licensed for use such as MPL (3-O-desacyl-4-monophosohryl lipid A), a detoxified bacterial lipopolysaccharide in aluminium salts, could be a promising source of novel adjuvants in veterinary vaccines [81].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Some studies demonstrated that certain strains of L. tropica cause mild pathogenesis in BALB/c mice characterized by small or no detectable swelling in the injection site, so measuring lesion size was not considered as a promising tool for the evaluation of vaccine efficiency as discussed by Fate-meh et al [17] and Rostamian et al [29]. In fact, in some cases, cutaneous lesions due to L. tropica may develop to ulcerative detectable lesions as discussed by Masoudzadeh et al [30], like the case in our study, so monitoring lesion size could strongly reflect the immune response obtained from the vaccines used.…”
Section: Discussionmentioning
confidence: 99%
“…photosensitization; 65 impairing the mannose activation pathway 66 ) and challenge have indicated promise but have not yet reached advanced phases of clinical development. [67][68][69] Targeted genetic modification to attenuate or delete specific virulence genes within Leishmania is considered a powerful strategy with the potential to provide crossprotective parasites with improved safety profiles, examples are described on Table 1. While the first attempts using attenuated Leishmania parasites rendered protection in murine models, lack of knowledge regarding potential reversion to a wild type genotype left the parasites unsuitable for use in human populations.…”
Section: First Generation Vaccinesmentioning
confidence: 99%